2009
DOI: 10.1007/s10461-009-9547-9
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Intentions of HIV-1 Infected and Uninfected Women in Malawi: A Longitudinal Study

Abstract: This study aimed to determine changes in fertility intentions of HIV-1 infected and uninfected reproductive age women in Blantyre, Malawi. Participants were asked about their fertility intentions at baseline and at 3-month visits for 1 year. Time-to-event statistical models were used to determine factors associated with changes in fertility intentions. Overall, 842 HIV uninfected and 844 HIV infected women were enrolled. The hazard of changing from wanting no more children at baseline to wanting more children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 20 publications
7
75
2
Order By: Relevance
“…While a third of women decided they no longer wanted children after HIV diagnosis, nearly half of them changed their mind once they had become aware of advances in HIV management and treatment. Decreased fertility intentions associated with HIV diagnosis have also been reported in other studies in the pre-HAART era (Bedimo et al, 1998;van Benthem et al, 2000;Stephenson and Griffioen, 1996;De Vincenzi et al, 1997), and more recently in Africa, where access to HAART remains limited (Taulo et al, 2009;Yeatman, 2009). Qualitative studies have shown that childbearing intentions in HIV-infected women are affected by personal health-related concerns, fear of transmitting HIV to the child, and societal influences and stigma (Craft et al, 2007).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While a third of women decided they no longer wanted children after HIV diagnosis, nearly half of them changed their mind once they had become aware of advances in HIV management and treatment. Decreased fertility intentions associated with HIV diagnosis have also been reported in other studies in the pre-HAART era (Bedimo et al, 1998;van Benthem et al, 2000;Stephenson and Griffioen, 1996;De Vincenzi et al, 1997), and more recently in Africa, where access to HAART remains limited (Taulo et al, 2009;Yeatman, 2009). Qualitative studies have shown that childbearing intentions in HIV-infected women are affected by personal health-related concerns, fear of transmitting HIV to the child, and societal influences and stigma (Craft et al, 2007).…”
Section: Discussionmentioning
confidence: 66%
“…Studies prior to the advent of highly active antiretroviral therapy (HAART) showed reductions in live birth rates and increases in termination rates after HIV diagnosis (Stephenson and Griffioen, 1996;van Benthem et al, 2000;De Vincenzi et al, 1997), but included little information on the women themselves. Likewise, in African settings where women have limited access to antiretroviral therapy, HIV diagnosis is associated with lower fertility intentions in HIVpositive than HIV-negative women (Kaida et al, 2010;Taulo et al, 2009;Yeatman, 2009). …”
mentioning
confidence: 99%
“…However, in some countries where the HIV prevalence rate is high, contraceptive use is reasonably low. High rates of unmet contraceptive need and unplanned pregnancy have been reported among HIV infected women in Malawi, South Africa, and Uganda [25][26][27][28] . In Uganda, the contraceptive prevalence rate among currently married women is 24% which is very low compared to the countries Ireland (89%), Norway (88%), etc.…”
Section: Discussionmentioning
confidence: 99%
“…56 Similar results have been reported from Malawi, where a study found HIV-positive women to be 61% less likely to desire pregnancy than their HIV-negative counterparts. 57 The limited evidence on HIV-positive men's pregnancy intentions generally indicates that HIV-positive men tend to want children more than their HIV-positive female counterparts. [36][37][38]52,58 More research is needed to explore men's and couples' views on pregnancy desires in the context of HIV.…”
Section: Hiv and Pregnancy Desiresmentioning
confidence: 99%
“…60 A recent study in Malawi found that while HIVpositive women desire pregnancy less than HIVnegative women, the rate of pregnancy after one year was not different between the two groups, suggesting unmet contraceptive need, non-use or failure of a contraceptive method, or inability to negotiate contraceptive use. 57 Unintended pregnancies among HIV-positive women contribute to pediatric HIV infections because only about half of HIV-positive women worldwide receive PMTCT interventions despite the scale-up of PMTCT services in recent years. 61 For HIV-positive women who do not wish to become pregnant, prevention of unintended pregnancies through access to voluntary family planning can contribute to improving maternal health as well as reducing pediatric HIV infections.…”
Section: Preventing Unintended Pregnancies Among Hiv-positive Womenmentioning
confidence: 99%